All-cause mortality in patients with medullary thyroid carcinoma of different ages: an inverse L-curve analysis study - Chen, Jiahua; Chen, Jiafei; Zhang, Mi; Hong, Yong (Frontiers in Endocrinology, 2025)
BackgroundMedullary thyroid carcinoma (MTC) is a malignancy with a high mortality rate and a wide age range. However, there are relatively few studies on the relationship between age and all-cause mortality in patients with MTC. As one of the important factors influencing cancer prognosis, the association between age and all-cause mortality in MTC patients needs to be further investigated.ObjectiveThe aim of this study was to investigate the relationship between age and all-cause mortality in MTC patients, especially whether there is an inverse L-shaped curve relationship, in order to provide new insights for clinical management and prognostic assessment.MethodsA detailed retrospective cohort analysis of 1291 MTC patients diagnosed between 2000 and 2021 was included in this study using the Surveillance, Epidemiology, and End Results (SEER) database. Cox regression modelling, curve fitting, Kaplan-Meier (KM) survival curves and subgroup analyses were used to assess the association between age and all-cause mortality in MTC patients. Potential confounders, including patient sex, race, Summary stage, surgery, Lymph.node.dissection, tumour size and lymph node metastasis (LNM), were rigorously controlled.ResultsThe risk of all-cause mortality in MTC patients increased by 6% per 1-year increase in age (hazard ratio HR=1.06, 95% confidence interval CI: 1.05-1.06, p<0.001). Further analysis revealed a significant inverse L-shaped relationship between age and all-cause mortality in MTC patients. Specifically, before the age of 50 years, the hazard ratio increased slowly with age (HR=1.024, 95% CI: 0.991-1.059) and the difference was not statistically significant (p=0.1616). After the age of 50 years, the hazard ratio accelerated with increasing age (HR=1.066, 95% CI: 1.051-1.081) and the difference was statistically significant (p<0.001).ConclusionThe results of this study confirm that there is an inverse L-shaped relationship between age and all-cause mortality in MTC patients. The risk of all-cause mortality in MTC patients increased significantly with age after age >50 years. This finding provides new insights into understanding the complex relationship between age and all-cause mortality in MTC, which may help inform clinical management and prognostic assessment.